Blurry vision: Supply chain visibility for personal protective equipment during COVID-19. Issue 3 (June 2021) - Finkenstadt, Daniel Joseph; Handfield, Robert
Abstract: We explore supply chain visibility challenges in the context of our contemporary COVID pandemic, and offer insights, models and potential solutions to remove barriers to clear supply chain visibility. In this paper, we describe how visibility and velocity are the two key attributes that are required to enabling critical decision-making accuracy which will in turn increase the ability of local, state and federal healthcare and public health decision-makers to response to shifts in the U.S. system. We describe the problems in current systems due to the lack of visibility of material in global supply chains, which in turn leads to problems such as the lack of PPE that occurred during the COVID pandemic. We conclude with recommendations on how to render inventory more visible for the future.